Nursing students’ knowledge regarding sexuality, sex, and gender diversity in a multicenter study - Santiago, Conceição; Guerra, Açucena; Carreira, Teresa; Palma, Sara; Bia, Florbela; Pérez-Pérez, Jorge; Frias, Ana; Gómez-Cantarino, Sagrario; Dias, Hélia (Frontiers in Psychology, 2024)
Sexuality is an integral part of development and personality, and is important in healthcare. Nurses are among the most representative healthcare professionals. For holistic and inclusive nursing care practice and to improve equality, human rights, well-being, and health of individuals, the curricula of nursing courses must integrate broad knowledge about sexuality and its diversity. This study aimed to identify and analyze nursing students' knowledge of sexuality, sex, and gender diversity. The present study was part of a multicenter study conducted in Europe.Methods: Questionnaires were administered in three nursing schools to assess nursing students' knowledge (n=75). Data processing was performed using Excel® software version 20 and IRaMuTeQ (R Interface pour les Analysis Multidimensionnelles de Textes et de Questionnaires) 0.7 alpha 2, allowing organization by category and subsequent thematic analysis using content analysis.The textual corpus "Nursing students' knowledge about sexuality in its diversity," was divided into two sub-corpus: "Students' perception of sexuality" and "Students' perception of gender identity," originating Class 6 "Eroticism" (14.23%) and Classes 4 "Sexual Orientation" (16.07%) and 3 "Heteronormative" (16.07%), the latter with greater proximity to each other and consequently to Class 6. Similarly, Classes 1 "Gender" (20.36%) and 5 "Cisgender" (12.14%) also presented a greater interrelationship between themselves and consecutively with Class 2 "Gender Identity" (15.36%).The analyses revealed that though nursing students possessed knowledge about sexuality and its diversity, this knowledge was elementary and did not reveal a sustained appropriation of This is a provisional file, not the final typeset article concepts related to sexuality, sexual orientation, and gender diversity. For some questions, the absence of students' answers were noteworthy, and may be associated with their personal reservation in expressing themselves on this sensitive and intimate theme. To ensure diversity, inclusivity, and impartiality in nursing practice, it is imperative to change the curriculum plans of nursing courses to address the theme of sexuality during the training process of nurses in Europe.